Quality of schooling and political trust among students - Hassan, Bilal (Frontiers in Political Science, 2025)
Political trust is a fundamental component of democratic stability, yet its relationship with the quality of schooling remains underexplored. This study examines how both student-level perceptions of schooling—measured through distributive justice, procedural fairness, and functional effectiveness—and national-level investment in education influence political trust across 22 European countries. Using data from Round 2 of the European Social Survey (2004) and national-level education expenditure from the World Bank (2004–2006), this study employs multilevel modeling to assess the impact of quality of schooling on political trust. The results reveal that students’ perceptions of distributive justice, procedural fairness and functional effectiveness significantly impact political trust, alongside national-level spending in education. These findings highlight the role of education in shaping political attitudes and suggest that government commitment to educational quality can enhance trust in political institutions. The study offers important implications for policymakers, particularly in the context of ongoing debates on education privatization and public investment in schooling.